APPLICATION OF BEHAVIOR LEARNING THEORY IN AN ATTEMPT UPGRADE TRUST STUDENT SELF - Ayu Puspa Devi; Neviyarni; Herman Nirwana (Yayasan Citra Dharma Cindekia, 2021)
Learn as a lasting change in observable behavior that occurs as a result of experience. Early research on classical behavioral learning studied the effect of stimulation on reflexive behavior. Contributes to the notion of classical conditioning, whereby an initially neutral stimulus (NS) becomes a conditioned stimulus (CS) that evokes a conditioned response (CR) because of its temporal proximity to an unconditioned stimulus (AS) that triggers a similar unconditioned response (UR). Behavioral application using a systematic approach to applying the principles of operant conditioning to modify student behavior is known as applied analysis. Confidence needs to be owned by every individual. Self-confidence is formed from the realization that if you decide to do something.